ALTERATION TUMOR NECROSIS FACTOR-ALPHA AND MATRIX METALLOPROTEINASE-9 EXPRESSION IN CANDIDA KERATITIS WITH AND WITHOUT STEROID ADMINISTRATION - VITRESIA, HAVRIZA; JAMSARI, JAMSARI; T, GONDHOWIHARDJO; EKA PUTRA, ANDANI (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to determine the severity level of keratitis, inflammatory response, and clinical feature of fungal keratitis associated with tumor necrosis factor-alpha (TNF-α) and matrix metalloproteinase (MMP)-9 expression, with and without steroid administration. Methods: The mice corneas were inoculated with 108 CFU Candida albicans (CA), divided into two groups, one group with steroid administration and other group without steroid, and uninoculated cornea is used as the control. The mice eyes were observed for the development of keratitis and assess the clinical score to categorize severity level of the keratitis. After 7 days, they were enucleated for analysis of TNF-α and MMP-9 expression with immunohistochemistry and histopathologic examination. Results: Results show that the group inoculated with Candida and steroid has more moderate and severe level of keratitis compared to the group inoculated with Candida only. The final clinical score in the group of CA injected with steroid was 5–12 with mean 8.89 (2.67). The histopathological examination confirmed the presence of prominent inflammatory response in steroid group. The mean of TNF-α expression in Candida keratitis with and without steroid injections is 50.1 (8.09) and 31.7 (6.89) consecutively, compared to 16.8 (1.58) of control group. The mean of MMP-9 expression in Candida keratitis with steroid injection is higher than Candida keratitis group without steroid injection and control group, which are 46.6 (4.3), 37.8 (4.96), and 17.2 (1.73), respectively. This difference is statistically significant. Conclusion: Administration of steroids to Candida keratitis has negative effect to corneal tissue, resulting in more severe inflammatory response associated with increased TNF-α and MMP-9 expressions.